Fabrication And Properties Of Multiwalled Carbon Nanotubes Filled Woven Glass Fibre Reinforced Epoxy Laminated Hybrid Composites - Ahmad, Wan Dalina Wan (2017)
Carbon nanotubes are commonly utilized in fabrication of hybrid composite laminates in order to manufacture lightweight composites. In this research, the multiwalled carbon nanotubes (MWCNT) was incorporated in glass fibre reinforced epoxy laminated composites by different methods. The MWCNT incorporated was either in the form of buckypaper (CNT sheet) or attached onto the glass fabrics by spreading and spraying methods. Buckypapers with MWCNT loading varied from 150 mg to 300 mg were prepared by vacuum filtration method at 30 kPa and 40 kPa pressures. Based on the characterization of the buckypaper, buckypaper which contained 150 mg of MWCNT and vacuum filtered at 30 kPa pressure was selected to be incorporated into the composite system. It was found that hybrid composites incorporated with epoxy-filled buckypaper (CNTBPE) improved the flexural strength by 63 % and 41 % higher compared to 3-ply GF/epoxy (3GF) and 4-ply GF/epoxy (4GF) laminated composite, respectively. However, incorporation of MWCNT by using buckypaper was unable to increase the glass transition temperature (Tg) of the hybrid composites. In fabrication of ink-facilitated MWCNT hybrid composites, it was found that 5.6 vol % was the optimum loading of the Chinese black ink in order to improve the dispersion and attachment of MWCNT onto the glass fabrics. Flexural strength and modulus of the hybrid composite of 1.4 vol % CNT and 5.6 vol % ink loading (CNT1.4/INK5.6) was increased by 106 % and 14 % compared to 4GF, respectively. However, insignificant increment in Tg is observed using this method. On the other hand, incorporation of 0.6 vol % of MWCNT by spreading method in ink-facilitated hybrid composites (CNT0.6) has improved the flexural strength and modulus by 219 % and 17 % higher compared to 4GF, respectively. CNT0.6 exhibited the highest mechanical properties with improved thermomechanical properties. Significant improvement in impact strength and interlaminar shear strength was also observed in CNT0.6. The spreading method was found to be the best method among other methods utilized it throughout this research. Such improvement in mechanical and thermomechanical properties showed that fabrication lightweight hybrid composites with enhanced performance have been achieved.